The first records of eleven species of the genus Megaselia Rondani, 1856 from Morocco (Diptera, Phoridae) - Fatima Zahra Sliman; R. Henry L. Disney; Kawtar Kettani (Check List, 2024)
We provide new records of scuttle ﬂies, family Phoridae (Diptera), from Morocco, which has been very little studied. Eleven phorid species belonging to the immense genus Megaselia Rondani, 1856 are newly reported from the country, increasing the number of known species in Morocco to 12, and the number of Phoridae to 14. Information on the distribution and ecology of each species is provided.